2002
DOI: 10.5326/0380515
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Effects of Intrathoracic Insufflation in Dogs

Abstract: This study was designed to quantify the effects of incremental positive insufflation of the intrathoracic space on cardiac output (CO), heart rate (HR), arterial pressure (AP), central venous pressure (CVP), and percent saturation of hemoglobin with oxygen (SPO2) in anesthetized dogs. Seven healthy, adult dogs from terminal teaching laboratories were maintained under anesthesia with isoflurane delivered with a mechanical ventilator. The experimental variables were recorded before introduction of an intrathorac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 17 publications
1
27
0
2
Order By: Relevance
“…These latter increases may have been because of sympathetic stimulation associated with decreased ventilation in 2 cats and a light plane of anesthesia. Central venous pressure and PAP were significantly higher compared to baseline at most time points probably because of the direct effect of the elevated intrathoracic pressure on central veins, a phenomenon also seen in canine and porcine models …”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…These latter increases may have been because of sympathetic stimulation associated with decreased ventilation in 2 cats and a light plane of anesthesia. Central venous pressure and PAP were significantly higher compared to baseline at most time points probably because of the direct effect of the elevated intrathoracic pressure on central veins, a phenomenon also seen in canine and porcine models …”
Section: Discussionmentioning
confidence: 74%
“…Thoracic CDI has been reported rarely in the veterinary literature perhaps because of the documented evidence that it causes significant cardiorespiratory compromise even at relatively low intrathoracic pressures . This is related to collapse of thin‐walled low‐pressure vascular compartments within the thorax (right atrium, caudal and cranial vena cava) under the effects of the insufflation pressure which limits cardiac preload . In conjunction with this, pulmonary resistance increases, which further decreases CI and SV .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OLV is possible in cats but technical challenges are encountered related to the small diameter of the feline large airways and the difficulty in establishing bronchoscopic visualization for positioning of specialized endotracheal tubes or blockers . Carbon dioxide insufflation has been used sparingly in dogs due to detrimental effects on cardiac output secondary to compression of low‐pressure vascular spaces within the thorax, even at very low intrathoracic pressures . The cardiopulmonary effects of low‐pressure carbon dioxide insufflation in cats have been investigated in conjunction with OLV but not in isolation .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that thoracic insufflation with carbon dioxide with or without associated abdominal insufflation causes cardiopulmonary effects such as decrease in oxygen saturation, arterial blood pressure and cardiac output, and increases in peak inspiratory and central venous pressure 22,23 . One study that mentions insufflation pressure for correction of diafragmatic rupture in clinical conditions used 10 mmHg.…”
Section: Discussionmentioning
confidence: 99%